Changes in migratory patterns of village youth: example of the village of Kać - Stojšin, Snežana S (Sociološki pregled, 2022)
The basic aim of the paper is the analysis of the changes in migratory patterns of village youth on the basis of the results of the longitudinal research conducted in the village of Kać in 1999 and 2021 respectively. In both research studies the same questionnaire was used for data comparability. In the ongoing 2021 research, whose preliminary results will be presented in this paper, we have added a few items due to the presupposition that there are changes in the migratory patterns of village youth. Namely, the basic presupposition is that the difference in the migratory patterns of village youth is primarily reflected in the changes of the desired target place or target country, i.e. that a larger number of young people want to go abroad today that twenty years ago, when larger cities in Serbia were favoured. Another presupposition is that pull and push factors have remained the same to a great extent. The analysis of the results indicates that external migrations, i.e. going abroad, are more appealing than in the first research period in 1999, when Novi Sad was the most desirable migration destination. However, the analysis of pull and push factors in both research studies offers almost identical results, where the poor financial situation and the failure to find any job or a job in their own profession are the main rejection factors among the village youth even twenty years later.
Keywords: village youth; migrations; migratory patterns; Kać; longitudinal research